Surgical Treatment of Venous Ulcer in The Lower Limbs - Cadillo Chávez, Ronald (1998)
OBJECTIVE: To find out the results of the surgical treatment performed in patients with venous ulcer (VU) in the lower limbs and to determine the varicose or venous nature of ulcers. MATERIAL AND METHODS: A retrospective study in 256 cases of VU of the lower limbs who underwent surgical treatment at the Hospital Edgardo Rebagliati Martins since 1986 to 1996, was made. RESULTS: Males (56,3%) were the most affected for VU. The most affected age group was between 35 and 64 years old. We found a varicose disease background in 67,2%. Traumatism (37,5%) was not the most common way of starting a VU. 41,6% of the patients underwent some kind of previous treatment, predominantly medical treatment (43,4%) followed by surgical treatment (26,4%). The most frequent symptoms were pain (76,6%), rush (28,9%), hyperpigmentation (22,7%) and edema (22,3%). Phlebographic examination was the main auxiliary method. The most frequent location was VU of the internal maleolar area (74,6%), followed by the leg medium third (12,9%). Four operational types were performed: 1. Dermoepidermical graft (DG), 2) Saphenectomy, 3)Saphenectomy plus DG, and 3) Perforant and collateral veins blockade associated to DG. The latter was the most successful one. The less desirable results were obtained with DG alone. CONCLUSIONS: In our study, the results obtained allowed us to state that, since the high rate of recovery, surgical treatment is a rational method to help us solving the problems related with this pathology.